THE STUDENT’S ABILITY AND PROBLEMS IN WRITING INTRODUCTION OF RESEARCH PROPOSAL - Kheryadi Kheryadi (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
This research aims to investigate the students’ ability and problems in writing introduction section of research proposal. This study has been conducted in an undergraduate English study program a University in Banten. The documentation/selection of students’ research proposal was conducted by choosing nine students’ research proposals from fifty seven students to represent different levels of achievement. It uses text analysis and in-depth interview to investigate the students’ performance in writing a research proposal. These findings implicate that most students faced difficulties in presenting arguments in terms of justifications. Second, most students were not aware that there are standard models in writing a research proposal, especially in terms of its elements and linguistic features, which are widely accepted in the field of English  Language  Teaching  (ELT). This study supports the extensive research into academic writing that emphasizes the importance of explicit teaching of the structure of specific written genres, particularly a research proposal, to second-language students.Keywords: Research proposal, Introduction section, Academic writing